Pembuatan Bioetanol Dari Nira Nipah Dengan Penambahan Tween 80 Dan Ergosterol Pada Proses Fermentasi Menggunakan Sacharomyces Cereviceae - Mohammad Rezky; Chairul Chairul; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Nypah sap is one of potential materials it’s processed into bioethanol. Availability of nypah palm land in Indonesia and a fairly high sugar content (15-20%) makes nipa sap has the potential it’s processed into bioethanol. Ergosterol is an essetial component of yeast cells that maintains the integrity of the membrane. It’s invetigated as an important factor the ethanol tolerance of yeast cells. Ethanol and hypoxia were found to have negative and synergistic effects on the total ergosterol contents of both strains and it’s significantly reduce the free ergosterol. Effect of a surfactant Tween 80 on the bacterial for growth, increase the glucose consumption rate at the later stage of the fermentation, maintain the intact structure of yeast S. Cereviceae. Preparation started by the yeast S. Cereviceae inoculum in the 10% of fermentation medium so that yeast an able to adapt and ready for fermentation. Fermentation place taked in batches with volume of 2 liters of fermentation medium, variations in the tween 80 and ergosterol and variations of fermentation at time 24, 36, 48, 60 dan 72 hours and then concentration of yeast 4 g/l. The stirring speed in 200 rpm and temperature of fermentation at room temperature (25-300 C)it’s selected conditions. Bioethanol concentrations has been analyzed by used gas kromatografi. The process of fermentation optimum conditions indicated in the addition of tween 80 10 ml and ergosterol 1 gram at the time of 72 hours having the initial sugar concentration of 161,81 mg/ml. concentration Bioethanol obtained in this condition at 20,47% (v/v). Keywords: Ergosterol, Nipa sap, Saccharomyces cerevisiae, Tween 80.